Evaluation of the effect of multidisciplinary simulation-based team training on patients, staff and organisations: protocol for a stepped-wedge cluster-mixed methods study of a national, insurer-funded initiative for surgical teams in New Zealand public hospitals. Issue 2 (19th February 2020) - Weller, Jennifer; Long, Jennifer Anne; Beaver, Peter; Cumin, David; Frampton, Chris; Garden, Alexander L; Moore, Matthew; Webster, Craig S; Merry, Alan
Abstract : Introduction: NetworkZ is a national, insurer-funded multidisciplinary simulation-based team-training programme for all New Zealand surgical teams. NetworkZ is delivered in situ, using full-body commercial simulators integrated with bespoke surgical models. Rolled out nationally over 4 years, the programme builds local capacity through instructor training and provision of simulation resources. We aim to improve surgical patient outcomes by improving teamwork through regular simulation-based multidisciplinary training in all New Zealand hospitals. Methods and analysis: Our primary hypothesis is that surgical patient outcomes will improve following NetworkZ. Our secondary hypotheses are that teamwork processes will improve, and treatment injury claims will decline. In addition, we will explore factors that influence implementation and sustainability of NetworkZ and identify organisational changes following its introduction. The study uses a stepped-wedge cluster design. The intervention will roll out at yearly intervals to four cohorts of five District Health Boards. Allocation to cohort was purposive for year 1, and subsequently randomised. The primary outcome measure is Days Alive and Out of Hospital at 90 days using patient data from an existing national administrative database. Secondary outcomes measures will include analysis of postoperative complications and treatment injury claims, surveys of teamwork and safety culture, in-theatre observations and stakeholder interviews. Ethics and dissemination: We believe this is the first surgical team training intervention to be implemented on a national scale, and a unique opportunity to evaluate a nation-wide team-training intervention for healthcare teams. By using a pre-existing large administrative data set, we have the potential to demonstrate a difference to surgical patient outcomes. This will be of interest to those working in the field of healthcare teamwork, quality improvement and patient safety. New Zealand Health and Disability Ethic Committee approval (#16/NTB/143). Trial registration number: Australian and New Zealand Clinical Trials Registry ID ACTRN12617000017325 and the Universal Trial Number is U1111-1189-3992.